Industrial Application of Rice Husk as an Alternative Fuel in Cement Production for CO2 Reduction - Bramantiyo, Ranoe; Lestianingrum, Erna; Cahyono, Rochim B (ASEAN Journal of Chemical Engineering, 2022)
The cement industry generally spends about 30-40% of production costs to provide energy for production. It forces the cement industry to look for cheaper and widely available alternative energy sources to increase its competitiveness. The dominance of fossil fuels poses another problem for the cement industry in the form of high CO2 emissions. To overcome this, PT Indocement Tunggal Prakarsa (ITP) Tbk, Palimanan Unit, is committed to continuously looking for alternative energy sources by utilizing rice husks in the suspension preheater unit. This study aims to evaluate the performance, especially the reduction of CO2 emissions and the economic benefits of energy substitution applications using rice husks. Based on the calculation in 2020, there will be an increase of 37% in 2021, and the total energy of rice husks will reach around 1,996,671 GJ. It is equivalent to using fossil fuel coal of approximately 106,450 tonnes. The contribution of rice husks to primary energy consumption seems to continue to increase yearly. A significant increase occurred between 2020 - 2021, and the contribution of rice husks reached 23%. Rice husks usage has reduced CO2 emissions by almost 220,000 tons of CO2e and brought production cost benefits to around 40 billion by 2021. Therefore, the substitution of coal fuel using rice husk has proven to be effective in reducing CO2 emissions in the cement production process. By still paying attention to the reliability of the process and the quality of the cement products produced, these efforts can be continuously encouraged to realize cement products that are more environmentally friendly.